The Influence of Teacher Readiness and Perceived Ease of Use of Artificial Intelligence on the Effectiveness of Digital Learning in Secondary Schools - Siti Khosiyah (CV. Era Digital Nusantara, 2026)
This study examines the influence of teacher readiness and perceived ease of use of Artificial Intelligence (AI) on the effectiveness of digital learning in secondary schools. The research addresses the growing need to optimize AI integration in education by focusing on human and technological factors that determine successful implementation. The objective of this study is to analyze the individual and simultaneous effects of teacher readiness and perceived ease of use on digital learning effectiveness. A quantitative approach with an explanatory survey design was employed. Data were collected through a structured questionnaire distributed to 198 secondary school teachers who have experience with digital learning technologies. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results reveal that teacher readiness has a positive and significant effect on digital learning effectiveness, indicating that teachers’ competence, confidence, and preparedness play a crucial role in enhancing instructional quality. Similarly, perceived ease of use significantly influences digital learning effectiveness, suggesting that user-friendly AI systems facilitate greater adoption and utilization in teaching practices. Furthermore, the combined effect of both variables demonstrates strong explanatory power, confirming that the integration of competent teachers and accessible technology leads to improved learning outcomes. The study also found an increase in digital learning effectiveness, particularly in student engagement and personalized learning. These findings highlight the importance of continuous professional development, user-centered technology design, and institutional support to maximize the benefits of AI in education.